Online Homestay Reservation System (OHRS) - Puteri Noor Ruzanna, Abd Aziz (2010)
Aims of this project are to study the needs of Homestay and to develop a prototype model for Homestay reservation process. This prototype will help the reservation process for the customer and also for the coordinator of the Homestay. By developing this project, it will help the coordinator to accelerate their business information properly either directly or indirectly. The development of this project also brings a big impact to the Homestay industries, where they can start promote their Homestay in an interactive ways. In addition the Object-Oriented System Analysis and Design are use as a methodology to develop the prototype. It is important to follow the step of the methodology to ensure the process of developing the prototype went smooth and the objectives of this project are achieved.